1999
DOI: 10.1046/j.1365-2249.1999.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and gender on serum dehydroepiandrosterone sulphate (DHEA-S), IL-6, IL-6 soluble receptor (IL-6 sR) and transforming growth factor beta 1 (TGF-β1) levels in normal healthy blood donors

Abstract: SUMMARYDysregulation of IL-6 synthesis is thought to play a role in the development of a number of age-related conditions, such as rheumatoid arthritis, osteoporosis, atherosclerosis, Alzheimer's disease and B cell malignancies. Recently it has been suggested that the production of IL-6 is in¯uenced by the adrenal hormone dehydroepiandrosterone (DHEA) and its sulphated derivative DHEA-S. In humans we investigated the relationship between DHEA-S, IL-6, IL-6 sR and TGF-b1 in the serum of normal healthy male and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
5
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 43 publications
8
61
5
1
Order By: Relevance
“…Cortisol in women using OAC was much higher than the other groups, which could be attributed to an elevated concentration of CBG induced by estrogens (39,40). The lower DHEAS concentrations in women than in men, and still lower concentrations in women using OAC, can be explained by the increased metabolic clearance induced by estrogens (41,42). This observation is supported by a randomized controlled trial in which introduction of OAC lowered adrenal androgen concentrations substantially (43).…”
Section: Discussionmentioning
confidence: 79%
“…Cortisol in women using OAC was much higher than the other groups, which could be attributed to an elevated concentration of CBG induced by estrogens (39,40). The lower DHEAS concentrations in women than in men, and still lower concentrations in women using OAC, can be explained by the increased metabolic clearance induced by estrogens (41,42). This observation is supported by a randomized controlled trial in which introduction of OAC lowered adrenal androgen concentrations substantially (43).…”
Section: Discussionmentioning
confidence: 79%
“…We found no relationship between age and the increased bronchial responsiveness to methacholine after exposure in a swine confinement building. The postexposure IL-6 serum levels seemed to increase rather than decrease with age (26) and therefore indicated that the lower increase in serum IL-6 levels after the exposure of the swine farmers (who were older than the nonfarmers) was due to their exposure history rather than to the different age distribution of the groups. In addition, in a study by Bruunsgaard et al (27), it was shown that ex vivo stimulation of blood with LPS resulted in significantly lower levels of TNFα and IL-1β in elderly humans when they were compared with young referents, whereas no difference was detected with regard to IL-6.…”
Section: Palmberg Et Almentioning
confidence: 94%
“…[30][31][32][33][34] Women, on the other hand, tend to exhibit higher risk than men in CRP (a marker of inflammation) levels and biomarkers representing neuroendocrine functioning. 30,[35][36][37] Other research has also shown gender differences in cumulative biological risk, with some studies showing men with higher overall levels 15,30 and other studies showing women across different populations with higher levels. 38,39 These combined findings suggest differential patterns of biological risk between men and women and warrant further examination of composite biological risk measures using gender-specific cutoffpoints.…”
Section: Introductionmentioning
confidence: 99%